Upper Ordovician ostracods from the Cautley district, northern England: Baltic and Laurentian affinities - Williams, M; Stone, P; Siveter, D; Taylor, P (2001)
The Cautley Mudstone Formation and Cystoid Limestone Member of the Ashgill Formation (Windermere Supergroup; Ashgill Series), from the Cautley district of northern England, has yielded an ostracod fauna of more than 30 species. Many of these have short ranges, permitting recognition of stratigraphically successive Pusgillian-lower Cautleyan, middle-upper Cautleyan, and Rawtheyan ostracod faunas. Several species are also known from the upper Ordovician of North America (Anticosti Island), Scotland (Girvan district) and the Baltic region (Estonia, glacial erratic boulders of northern Germany), providing evidence to correlate upper Ordovician successions in these areas. The ostracods include abundant podocopes, at some horizons accounting for more than 80% of the fauna. Binodicopes are also common, but palaeocopes are rare. Assemblages are typical of a clastic dominated open marine shelf setting. Diversity at most horizons is low (c. 3-5 species), but reaches a peak of between 13-14 species in middle Cautleyan horizons. Lower diversity at Pusgillian and Rawtheyan horizons coincides with the encroachment of deeper marine-shelf facies which were probably hostile to Ordovician benthonic ostracods. Some of the ostracods (particularly Aechmina) have distributions suggesting tolerance of a range of mid- to deep shelf benthonic palaeoenvironments, but none were pelagic. During Ashgill times the Cautley district (part of palaeocontinental Avalonia) was replete with ostracod genera and species which also occur in the Baltic region (palaeocontinental Baltica; more than 90% generic similarity) and to a lesser, but nonetheless significant extent in North America and Scotland (parts of palaeocontinental Laurentia). Such trans-Tornquist Sea and Iapetus Ocean distributional patterns add to previous ostracod data that support models which show palaeogeographical proximity of Avalonia and Baltica, and Avalonia and Laurentia, by Ashgill times. The widely cited observation, that trans-lapetus ostracod faunas remained strictly provincial until the mid- or late Silurian, cannot be sustained.